FROM PLASTIC CRISIS TO CIRCULAR TOURISM: WASTE GOVERNANCE FAILURES AND SUSTAINABLE TOURISM PATHWAYS IN BALI, INDONESIA - I Nengah Suardhana; I Wayan Kartimin; I Gusti Bagus Rai Utama (Bajang Institute, 2026)
Bali’s tourism‑led growth has created a paradox in which rapid economic gains coexist with worsening plastic pollution, recurrent urban flooding, and degradation of the coastal and marine ecosystems that sustain its appeal as a destination. Despite the adoption of a 2019 single‑use plastic ban and source‑based waste management policies, plastic waste volumes remained largely stagnant at about 408–414 tons per day between 2017 and 2019, exposing persistent implementation gaps. This study examines how waste governance failures, stakeholder behaviour, and tourism dynamics interact to shape Bali’s plastic crisis, and evaluates the potential of circular‑economy and community‑based tourism models to shift current trajectories. Using a mixed‑methods approach, it combines district‑level statistics, policy and secondary data, and qualitative evidence from interviews and observations with communities, tourism businesses, informal waste workers, and officials. The findings highlight inadequate infrastructure, fragmented multi‑level governance, weak enforcement, and low segregation at source, with only roughly half of waste properly managed and about 11% of plastic leaking annually to rivers and the ocean. At the same time, eco‑village and circular initiatives achieve 20–25% waste reductions in pilot areas, signalling the viability of polycentric, community‑driven approaches aligned with SDGs 11, 12, 14, and 17. The study integrates political ecology, implementation gap, collective‑action, and circular‑economy perspectives and proposes a multi‑stakeholder governance framework, emphasising stronger source‑based segregation and TPS3R, scaled‑up circular tourism villages, context‑specific deposit‑return and extended producer responsibility schemes, and enforceable sustainability standards in the tourism value chain.